2015
DOI: 10.1016/j.leaqua.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

How do you really feel? Effect of leaders' perceived emotional sincerity on followers' trust

Abstract: We extend research on leadership and emotions by addressing two previously under-researched areas. Prior research has focused primarily on the valence of leaders' displayed emotion and on followers' affective reactions to those displays. In contrast, we examined followers' cognitive reactions to the perceived sincerity of leaders' displayed emotion. Study 1 found that American workers' trust in a leader was related to their perceptions of that leader's emotional sincerity. Study 2 replicated these results amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 88 publications
3
36
0
Order By: Relevance
“…Similarly, leaders must be cognizant that they will lose their influence and credibility with their constituents when they lie or are deceptive (dishonest); offer opinions and suggestions that are outside of their areas of competence; indicate verbally or nonverbally that they are bored, jaded, worn‐down, or beaten‐up by workplace demands; or appear to have lost faith in the vision or the pathway going forward. In any of these ways, the example set by the leader permeates the culture of the work team and can either enhance or hinder their actions and performance (Afsar, Badir, Saeed, & Hafeez, : Berson & Linton, ; Caza, Zhang, Wang, & Bai, ; Kouzes & Posner, , Zhu, May, & Avolio, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, leaders must be cognizant that they will lose their influence and credibility with their constituents when they lie or are deceptive (dishonest); offer opinions and suggestions that are outside of their areas of competence; indicate verbally or nonverbally that they are bored, jaded, worn‐down, or beaten‐up by workplace demands; or appear to have lost faith in the vision or the pathway going forward. In any of these ways, the example set by the leader permeates the culture of the work team and can either enhance or hinder their actions and performance (Afsar, Badir, Saeed, & Hafeez, : Berson & Linton, ; Caza, Zhang, Wang, & Bai, ; Kouzes & Posner, , Zhu, May, & Avolio, ).…”
Section: Discussionmentioning
confidence: 99%
“…Clark and Payne (2006) identify a strong relationship between perceptions of ability, integrity, fairness and openness to the other, on the part of the follower, as determining factors for the construction of relationships of trust in the leader. Caza (2015) confirms that trust in the leader increases as the subordinate realizes the leader's emotional honesty. Although these studies confirm some variables as antecedents of trust in the leader, we observe that these vary and need to be understood in their specific context.…”
Section: Trust Relations Leader-followersmentioning
confidence: 62%
“…The examinations of the inferences that followers make from observing the emotions of their leaders are rare, and none have been found that directly observe the upper lip. However, recently Caza, Zhang, Wang, and Bai, [ 86 ] identified that followers make judgments about leaders’ trustworthiness and emotional sincerity from the observation of their emotions. In terms of trustworthiness, followers may be attempting to determine the level of ability and competence of their leader [ 87 ] through the observation of emotions [ 88 ].…”
Section: Discussionmentioning
confidence: 99%